EFEKTIVITAS PEMBIAYAAN MIKRO SYARIAH DALAM PENGEMBANGAN USAHA KECIL DAN MENENGAH - Sandika, Tegar Aji (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to analyze the effectiveness of Islamic microfinance in developing Small and Medium Enterprises (SMEs) within the environment of Pondok Pesantren Imam Syafi’i Brebes. Using a quantitative approach, data were collected through questionnaires from 100 SME respondents who received financing from Islamic Microfinance Institutions (LKMS) under the pesantren’s management. Simple linear regression analysis shows that Islamic microfinance has a positive and significant effect on SME development, with a significance value of 0.000 and a coefficient of determination (R²) of 0.375. This means that Islamic microfinance can explain 37.5% of the variation in business development. In addition to funding, business mentoring and financial education also contribute to empowering the economy of santri and the surrounding community. The challenges identified include delayed disbursement, low literacy of sharia contracts, and mismatch between financing amounts and business needs. These findings highlight the importance of increasing funding capacity, providing intensive mentoring, and enhancing sharia-based financial literacy to optimize the benefits of Islamic microfinance